Differences in Glucose Metabolism Among Women With Spinal Cord Injury May Not Be Fully Explained by Variations in Body Composition - Li, Jia (Arch Phys Med Rehabil, 2018)
OBJECTIVE: To investigate the differences in glucose metabolism among women with paraplegic, and tetraplegic spinal cord injury (SCI) in comparison to their able-bodied (AB) counterparts after adjusting for differences in body composition. DESIGN: Cross-sectional study. After an overnight fast, each participant consumed a 75-g glucose solution for oral glucose tolerance test (OGTT). Blood glucose, insulin, and C-peptide concentrations were analyzed before and 30, 60, 90, and 120 minutes after ingesting glucose solution. Insulin sensitivity index (ISI) was estimated using the Matsuda index. Percentage fat mass (%FM) and total body lean mass (TBLM) were estimated using data from dual-energy x-ray absorptiometry. Visceral fat (VF) was quantified using computed tomography. Outcome measures were compared among groups using analysis of covariance with %FM (or VF) and TBLM as covariates. SETTING: Research university. PARTICIPANTS: Women (N=42) with SCI (tetraplegia: n=8; paraplegia: n=14) and their race-, body mass index-, and age-matched AB counterparts (n=20). INTERVENTIONS: Not applicable. RESULTS: At fasting, there was no difference in glucose homeostasis (glucose, insulin, C-peptide concentrations) among 3 groups of women. In contrast, glucose, insulin, and C-peptide concentrations at minute 120 during OGTT were higher in women with tetraplegia versus women with paraplegia and AB women (P<.05, adjusted for TBLM and %FM). In addition, women with tetraplegia had lower ISI (P<.05, adjusted for TBLM and %FM) versus AB women. These differences remained after adjusting for VF and TBLM. CONCLUSION: Our study confirms that impaired glucose metabolism among women with tetraplegia may not be fully explained by changes in their body composition. Future studies exploring additional factors involved in glucose metabolism are warranted.